An Anglo-Saxon Great Hall Complex at Sutton Courtenay/drayton, Oxfordshire: A Royal Centre of Early Wessex? - Hamerow, H; Brennan, N (Taylor and Francis, 2015)
An archaeological evaluation at the site of an Anglo-Saxon ‘great hall complex’ at Sutton Courtenay/Drayton (NGR 448733, 193671), previously known primarily from aerial photographs and metal-detector finds, included the partial excavation of two large timber buildings. One of these proved to be the largest Anglo-Saxon ‘great hall’ yet identified and had been cut into a prehistoric mound or bank. The smaller building overlay an earlier sunken-featured building of probable sixth-century date. The geophysical survey and excavation provide significant new information regarding the site, which is probably that of an undocumented royal centre associated with the earliest rulers of the West Saxons.